Consumer Confusion in the German DSL Market. - Neigenfind, Simone (2006)
As a result of the ever increasing amounts of information consumers can access for a proliferating product variety as well as shorter product-life-cycles, especially in terms of technology-based goods and services, the notion of consumer confusion is becoming increasingly important in todays highly competitive marketplace.